Perbedaan Kualitas Tidur Bayi Usia 3-12 Bulan Sebelum Dan Sesudah Diberikan Baby Massage - Dewi, Sang Ayu Yunda Setia; Tedjasulaksana, Regina; Suarniti, Ni Wayan (Jurnal Midwifery, 2026)
Introduction Lack of sleep was considered one of the main sources of disease burden in low- and middle-income countries. One of the factors that affected infant growth and development was sleep, but it was estimated that more than 72% of parents did not consider sleep disturbances in infants to be a problem. Sleep quality was influenced by several factors, including adequate rest, environment, physical activity, nutrition, and illness. This study aimed to find out the difference in sleep quality of infants aged 3–12 months before and after receiving baby massage therapy at the Independent Midwife Practice of Putu Sri Widi Antari, S.Tr.Keb. Method The research used a pre-experimental method with a one-group pre-test post-test design and no control group. A non-probability sampling approach with purposive sampling was applied. The sample consisted of 32 infants aged 3–12 months. Result The analysis showed that before receiving baby massage therapy, 4 infants (12.5%) had good sleep quality, and 28 infants (87.5%) had poor sleep quality. After the massage, 21 infants (65.6%) had good sleep quality, and 11 infants (34.4%) had poor sleep quality. Conclusion Based on the results of the Wilcoxon Signed Rank Test, the p-value was 0.000 < 0.050, so it was concluded that there was a significant difference in the sleep quality of infants aged 3–12 months before and after receiving baby massage therapy at the Independent Midwife Practice of Putu Sri Widi Antari, S.Tr.Keb. It is hoped that parents can apply baby massage to their babies to improve the baby's sleep quality, so that the baby's growth and development can be optimally fulfilled.